Evaluasi Pelayanan Swamedikasi oleh Tenaga Teknis Kefarmasian di Apotek X Kota Tangerang - Rangka, Febbyasi Megawaty; Sinurat, Selvina; Andriyania, Andriyania; Novia, Jessica; Munthe, Sri Wahyu Ningsih (JFIOnline | Print ISSN 1412-1107 | e-ISSN 2355-696X, 2025)
Self-medication or self-treatment is one way to treat diseases experienced without a doctor's prescription. Limited public knowledge about drugs can cause medication errors from drug selection, drug dosage and how to use drugs. Drug abuse and inappropriate drug use are often because the public does not get education or pharmacists give wrong drug recommendations. This study aims to evaluate the implementation of self-medication services by TTK at Pharmacy X, Tangerang City and the drug recommendations given. Quantitative research method with a prospective descriptive approach. Data were obtained through direct observation using a form on self-medication services by 6 TTK for 30 working days from February 1 to March 2, 2021. The sample consisted of 105 consumers who bought drugs without a doctor's prescription and the data was analyzed descriptively using Microsoft Excel with percentage calculations. The results of the study showed that consumer characteristics were dominated by men 55.24% and adults aged 26-45 years 46.67%. The implementation of self-medication that was not carried out 100% was the method of using drugs 55.23% and storing drugs 0%. The most common complaint was a dry cough in 20 cases (19.05%) accompanied by flu in 10 cases, colds in 6 cases, itchy throat in 3 cases and stomach ulcers in 1 caseInconsistency of drug recommendations occurred in complaints of dry cough, namely drugs containing guaifenesin indicated for phlegmy cough in 9 cases and phlegmy cough containing dextromethorphan HBr in 1 case which is an antitussive that can inhibit the cough reflex to expel phlegm. This shows a lack of understanding by TTK regarding the composition of drugs according to complaints and drug indications. TTK self-medication services need to be improved, especially aspects of drug storage education and drug recommendations based on complaints to minimize medication errors and improve the quality of pharmaceutical services at the community level.